Radical resection for duodenal carcinoma with isolated bilateral ovarian metastasis: a case report - Soni, Subhash; Varshney, Vaibhav; Goyal, Manu; Shekher, Shashank (International Surgery Journal, 2019)
Natural history of duodenal adenocarcinoma is not well known. Although extremely rare, the incidence of primary small bowel adenocarcinoma has been increasing. Primary duodenal cancer is a very rare, which has accounted for only 0.3% of all gastrointestinal cancers. Isolated ovarian metastasis from duodenal carcinoma is extremely rare entity. We report a case of duodenal carcinoma with isolated bilateral ovarian metastasis in a 39-year-old female patient managed surgically with Whipple’s procedure with bilateral oophorectomy. She presented with complaints of dyspepsia and intermittent vomiting since 1½ years. History of anorexia and weight loss present. Upper gastrointestinal endoscopy was suggestive of circumferential ulcerated friable lesion at duodenum (D1-2) region and histopathology suggestive of moderately differentiated adenocarcinoma. Subsequent imaging studies revealed 6×5 cm duodenal mass in D1 and D2 without IHBRD with right ovarian mass. She underwent staging laparoscopy with open classic Whipple’s procedure with bilateral oophorectomy was done. Intraoperatively 6×6 cm mass involving first and second part of duodenum involving head of pancreas was found with 3×3 cm right ovarian mass. Post-operative period was uneventful and she discharged on POD6. Final biopsy was suggestive of moderately differentiated adenocarcinoma of duodenum with bilateral ovarian metastasis and she received adjuvant chemotherapy. Now at 1 year, on regular follow up she is completely asymptomatic and imaging showed no recurrent disease. Isolated ovarian metastasis may not be a contraindication for radical surgery in selected group of patients with duodenal carcinoma.